PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA DENGAN MODEL PBL MELALUI MEDIA VISUAL PADA SISWA KELAS IV SD N SIDOREJO 01 TAHUN 2023/2024 - Naning Septilia Rahmawati; Raras Setyo Retno; Ninik Marginingsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to measure improvements in Pancasila education learning outcomes using the Problem Based Learning (PBL) learning model through visual media for class IV students at Sidorejo State Elementary School 01 in 2023/2024. The subjects of this research are class IV students at Sidorejo State Elementary School 01 totaling 21 students, with 6 female students and 15 male students. This research was conducted because class V students at SD Negeri Sidorejo 01 Sidorejo 01 had not yet reached the predetermined learning achievement indicators. To overcome this problem, learning improvements were carried out using the Classroom Action Research (PTK) method with two cycle stages. Increasing student learning outcomes in Pancasila Education subjects is not the same as using the Problem Based Learning (PBL) learning model through visual media in each cycle, which can be seen from the average student learning outcome score in cycle 1 is 73.71 with a completion percentage of 47. .61%. In cycle 2, there was an increase in the average learning outcome score to 79.47 with a completion percentage reaching 80.95%. The results of this research show that using the Problem Based Learning (PBL) learning model through visual media for students significantly increases the learning outcomes of Pancasila Education in class IV